Aural single‐word and aural phrasal verb knowledge and their relationships to L2 listening comprehension. Issue 1 (30th March 2022) - Cheng, Junyu; Matthews, Joshua; Lange, Kriss; McLean, Stuart
Abstract: This study quantifies second language (L2) knowledge of aural single words and aural phrasal verbs (PVs) and investigates their relationship with L2 listening comprehension. An aural first language (L1) meaning recall test format was used to measure knowledge of 81 single‐word and 81 PV target items (with equivalent frequencies of occurrence) among 224 Chinese tertiary‐level learners of English as a Foreign Language (EFL). Participants' L2 listening was measured with a version of the Test of English for International Communication (TOEIC). Participants' aural single‐word and aural PV knowledge were compared, and their relationship with L2 listening were examined using correlation and multiple regression analysis. These analyses also included comparison between participants of relatively high (Independent Users) and relatively low (Basic Users) L2 listening proficiency. Although regression modelling showed that single‐word test scores were most predictive of L2 listening comprehension, it also showed that PV test scores made a substantial contribution to the model's predictive capacity. In combination, single‐word and PV test scores could predict 42.7% of the variance observed in the listening scores. The theoretical and practical implications of these results are discussed.